Effect of the Dog positioning on X-Ray Table on Hip Dysplasia Parameter Evaluation - Martins, João; Colaço, Bruno; Alves-Pimenta, Sofia; Gonzalo Orden, José M.; Ferreira, António J.; Ginja, Mário M. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate the effect of pelvic tilting along the long axis and femoral rotation on Norberg angle (NA), subluxation index (SI) and subluxation category (SC) in the standard ventrodorsal hip extended (VDHE) radiographical view on live animals.Study Type This was a retrospective clinical study.Materials and Methods Pairs of VDHE views, one adequately positioned and the other with pelvic tilting or femoral internal or external rotation, were compared for the NA, SI and SC.Results On the malpositioned pelvis set, on the underside the mean ± SD NA was 98.7 ± 6.1°, the SI was 0.27 ± 0.12 and the SC was 2.8 ± 0.8 versus, on the acceptable set, the NA was 99.2 ± 6.4° (p > 0.05), the SI was 0.25 ± 0.12 (p < 0.05) and the SC was 2.3 ± 0.9 (p < 0.05); on the malpositioned upperside, the NA was 102.1 ± 6.4°, the SI was 0.21 ± 0.14 and the SC was 1.7 ± 1.1 versus, on the acceptable positioned set, the NA was 100.8 ± 6.7° (p < 0.05), the SI was 0.24 ± 0.15 (p < 0.05) and the SC was 2.3 ± 1.2 (p < 0.05). Femoral internal or external rotation sets did not show significant differences between malpositioned and acceptable positioned sets (p > 0.05).Conclusions In clinical practice, pelvic tilting along the long axis in VDHE view results in non-favourable hip changes in the NA, SI and SC on the underside and favourable on the upperside, and the internal or external femoral rotation did not affect these variables.
Keywords: Norberg angle; subluxation index; subluxation category; pelvic tilting; femoral rotation